The Change of Ciliary Muscle-Trabecular Meshwork-Schlemm Canal Complex after Phacoemulsification using Swept-Source-Optical Coherence Tomography - Zhangliang Li; Xueer Wu; Xinpei Ji; Zehui Zhu; Nan Zhe; Yun-e Zhao (Ophthalmic Research)
Introduction: Cataract surgery has been reported to have a reducing effect on intraocular pressure (IOP) in glaucomatous and non-glaucomatous eyes. This effect seems to be more noticeable in eyes with narrow angles (NAs) than in eyes with open angles (OAs). Decrease in IOP may be a result of the increase in anterior chamber angle and Schlemm canal (SC) after cataract surgery. The purpose of this paper was to evaluate the relationship between Schlemm canal-cross-sectional area (SC-CSA) changes and trabecular meshwork, ciliary muscle changes after cataract surgery and the difference in non-glaucomatous eyes with NAs and OAs. Methods: IOP, SC-CSA, Schlemm canal diameter (SCD), trabecular meshwork width (TMW) and thickness (TMT), trabecular-iris angle at 500 µm from the scleral spur (TIA500), and the distance between the inner apex of the ciliary muscle and scleral spur (IA-SS) were measured by swept-source-optical coherence tomography preoperatively and 1-week post-surgery. Patients were divided into NA and OA groups according to the degree of TIA500, and SC-CSA-related parameters were compared. Results: Seventy-five patients (89 eyes) were included. IOP significantly decreased, SC-CSA, SCD, TMW, TMT, and TIA500 significantly increased post-surgery (p < 0.001). Changes in nasal SC-CSA were associated with TMW (p = 0.003) and TIA500 (p < 0.001) changes; changes in temporal SC-CSA were associated with TMW (p = 0.001) and TMT (p < 0.001) changes. SC-CSA expansion was correlated with changes in TMW (β3.726 ± 1.085, p = 0.001 nasally; β3.405 ± 0.945, p = 0.001 temporally), TMT (β5.224 ± 2.033, p = 0.012 nasally; β11.853 ± 3.059, p < 0.001 temporally), and TIA500 (β40.330 ± 15.100, p = 0.009 nasally; β35.453 ± 17.527, p = 0.047 temporally). There was no association between SC-CSA expansion and IA-SS changes. SC-CSA expansion was greater in the NAs than in the OAs group (p < 0.001). Conclusion: Cataract surgery results in IOP reduction and SC-CSA expansion. Increased SC-CSA correlates with increases in TMW, TMT, and TIA500. SC-CSA increased more in NAs than in OAs group post-surgery, which may explain the greater decrease in IOP in eyes with NAs.